2017
DOI: 10.1149/07527.0089ecst
|View full text |Cite
|
Sign up to set email alerts
|

Development of Self-Healing Coatings with Micro Capsules for Corrosion Protection of Metal

Abstract: Self-healing coatings with capsules containing healing agents have been developed for the corrosion protection of metal. In this paper, polyurethane capsules were synthesized under different conditions to examine the size and shape of capsules, and selfhealing ability of coatings with capsules dispersed was examined after damaging the coated layer by scratching with a cutter blade.The size and shape of capsules depended on the concentration of chlorobenzene in cyclohexanone used as a solvent of prepolymer solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…During the process, prepolymer reacts with glycerol to form polyurethane capsules containing healing agents of IPDI, cyclohexanone and xylene. 5,6) In this solution, the amounts of prepolymer, IPDI, cyclohexanone, and xylene were 10.0 g, 9.5 g, 6.5 g, and 9.9 g, respectively.…”
Section: Formation Of Capsules Including Healing Agentsmentioning
confidence: 91%
“…During the process, prepolymer reacts with glycerol to form polyurethane capsules containing healing agents of IPDI, cyclohexanone and xylene. 5,6) In this solution, the amounts of prepolymer, IPDI, cyclohexanone, and xylene were 10.0 g, 9.5 g, 6.5 g, and 9.9 g, respectively.…”
Section: Formation Of Capsules Including Healing Agentsmentioning
confidence: 91%
“…This procedure was conducted via the oil-in-water emulsification process [ 22 ]. Based on previous studies, experimental parameters such as agitation rate and temperature have been demonstrated to affect the morphology, core content and size distribution of the microcapsules [ 30 , 31 , 32 ]. In addition, several studies have also reported on the agglomeration problem during the encapsulation process [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%